Tradisi Njamu dan Dunia Laki-laki Masyarakat Desa Banjardowo (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Njamu is a tradition to drink wine that has long been known to the communities in Banjardowo, Kradenan, Grobogan. People supporting this tradition view that in the tradition embodied the traditional values that can not be replaced by other cultures, although other normative people who live in the environment view that this tradition is a deviation that violates the norms. The purpose of this study is to address the following issues: (1) how is the tradition of njamu in the communities in Banjardowo Kradenan Grobogan (2) what factors are causing the appearance and survival of njamu tradition in the communities of Banjardowo. This study uses qualitative methods with the research subjects were the villagers of Banjadowo. Data collection techniques used were observation, interviews and documentation. The validity of the data is tested using data triangulation technique. The results showed that (1) The tradition of njamu is a phenomenon that has become a habit for abangan society in Banjardowo village, and is only done by men. Njamu activity patterns can be done individually and communally. (2) Njamu tradition still survive today since the local community see that njamu has a number of functions related to physical, social, economic and cultural function. From the results of research and discussion, it can be concluded that njamu persisted since it is interpreted as a tradition inherited from the ancestors, as well as being an effective social arena in representing men's world in the community.